2019
DOI: 10.1037/apl0000329
|View full text |Cite
|
Sign up to set email alerts
|

Transactive memory systems in context: A meta-analytic examination of contextual factors in transactive memory systems development and team performance.

Abstract: Research on transactive memory systems (TMS) has been conducted in a variety of teams, a range of task types and increasingly, in settings around the world. Despite this proliferation, there has been relative inattention to contextual factors that produce TMS and explain heterogeneity in the TMS to team performance relationship. TMS studies are typically conducted in homogeneous settings (i.e., teams located in a single country) and often with sources of potential variation (i.e., environmental volatility, lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
87
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 98 publications
0
87
0
Order By: Relevance
“…Correspondingly, we have identified that in periods of high stress there was a reliance on previous experience, or the experience of colleagues in the vicinity. The latter suggests that team dynamic and experience is an important resilience factor in PICU and may be as important as written guidelines 29. Team structure and team working in PICU is worthy of further comment in relation to prescribing.…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, we have identified that in periods of high stress there was a reliance on previous experience, or the experience of colleagues in the vicinity. The latter suggests that team dynamic and experience is an important resilience factor in PICU and may be as important as written guidelines 29. Team structure and team working in PICU is worthy of further comment in relation to prescribing.…”
Section: Discussionmentioning
confidence: 99%
“…Last but not least, even though many studies adopted Chinese firms as their research settings and samples [81,82], we still need to pay attention to the cultural effects as we try to generalize our finds. In the most recent study of Bachrach et al [56], they explored cultural effect using meta-analysis and found that some cultural contexts such as power distance and in-group collectivism can influence the TMS and performance relationships. In the future study, adopting multi-cultural samples may be helpful to generalize our finds.…”
Section: Discussionmentioning
confidence: 99%
“…Based on COR, the motivation for investing resources to gain more could provide individual “reason-to” perform proactively. According to the literature, TMS as a knowledge and human capital resource pool is associated with team performance [55] and team innovation [56]. In addition, TMS provides a trustworthy and knowledge-sharing environment, and such a trust relationship and effective information exchange quality would lead to high individual creativity [57].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Specialization refers to the existence of specialized knowledge in teams; reliability refers to team members’ belief regarding whether others’ knowledge is reliable; coordination refers to the team’s ability to smoothly and effectively coordinate knowledge (Wegner, 1987). Research has demonstrated that a well-developed TMS offers many potential benefits for team performance (Lewis, 2004; Zhang et al, 2007; Bachrach et al, 2019). First, TMS helps to increase team performance by allowing team members to quickly become familiar with people, tasks, knowledge, and problems (Liang et al, 1995).…”
Section: Hypotheses Developmentmentioning
confidence: 99%